Teoretichesike aspects of modeling wear layered coating - Artemchuk, V. V. (Science and Transport Progress, 2012)
In this paper we examine the effect of physico-mechanical properties of materials on the wear of the contacting pairs. The results of theoretical modeling of wear and tear, when the surface layer is composed of several layers with different characteristics, which may get in the recovery of parts. Based on theoretical models are examples of wear and tear contact of two bodies, each of which has a multilayer structure of the coating.